USE OF SPIROMETRY IN DETECTING AIRWAY OBSTRUCTION IN ASYMPTOMATIC SMOKERS: Spirometry in Asymptomatic Smokers - Bangash, Maj Mussavir Hussian; Zaidi, Syed Badshah Hussain; Zaidi, Syed Mohammad Asad; Khan, Imran (Pakistan Armed Forces Medical Journal, 2010)
Objectives: To detect spirometric abnormalities in asymptomatic smokers in relation to duration of smoking. Study Design: Cross sectional study. Place and Duration of Study: The study was carried out at PNS Shifa from Oct 2006 to June 2007. Subjects and Methods: Hundred individuals were included in this study who fulfilled the required criteria. Spirometry was done after briefing the patient about the procedure. Smokers were divided into two groups. Group I (5 to 9 pack years) and group II (≥ 10 pack years). All relevant information were recorded on Performa (Annex-A). The data was analyzed through SPSS-10, in terms of Mean ± SD (Standard Deviation) for numeric response variables and independent sample T test was applied to compare significance of proportion for numeric response variables at p < 0.05. Categorical variables were compared by applying Chi-square test at p < 0.05 level of significance. Results: Significant statistical difference was found between the mean age in the two groups with p-value of 0.011. This may be due to the longer duration of smoking history in Group II. Strong association was found between number of cigarette smoked and the pattern of airway obstruction as significant statistical difference of airway obstruction and early airflow limitation was found between the two groups of smokers at p value of 0.004. Conclusion: There is strong association between duration of smoking and development of airway obstruction even before the smoker become symptomatic.